2009
DOI: 10.1002/dvdy.21861
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion molecule L1 affects the rate of differentiation of enteric neurons in the developing gut

Abstract: The enteric nervous system arises predominantly from vagal level neural crest cells that migrate into and along the developing gut. As the neural crest-derived cells migrate within the gut, a subpopulation begins to differentiate into enteric neurons. Here, we show that the differentiation of neural crest-derived cells into enteric neurons is delayed in L1-deficient mice, compared with littermate controls. However, glial cell differentiation is not affected in L1-deficient mice. These mice also show a delay in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…However, it should be noted that, since the incidence of HSCR is low in L1 syndrome patients (about 3%) but probably higher in patients with X-linked hydrocephalus [60], L1 mutations alone are probably not sufficient to cause HSCR. Recently, a role for L1 in HSCR onset has been further supported by histological studies in L1-deficient mice, which showed that changes in the migration and differentiation of neural crest-derived cells within the developing enteric nervous system indeed depend on L1 [65,66]. Taken together, the available data suggest that L1 is a genetic modifier of HSCR.…”
Section: L1 Syndrome In Combination With Hirschsprung's Diseasesupporting
confidence: 59%
“…However, it should be noted that, since the incidence of HSCR is low in L1 syndrome patients (about 3%) but probably higher in patients with X-linked hydrocephalus [60], L1 mutations alone are probably not sufficient to cause HSCR. Recently, a role for L1 in HSCR onset has been further supported by histological studies in L1-deficient mice, which showed that changes in the migration and differentiation of neural crest-derived cells within the developing enteric nervous system indeed depend on L1 [65,66]. Taken together, the available data suggest that L1 is a genetic modifier of HSCR.…”
Section: L1 Syndrome In Combination With Hirschsprung's Diseasesupporting
confidence: 59%
“…Indeed, murine studies revealed L1 as a modifier gene in intestinal aganglionosis that is consistent with HSCR (Wallace et al 2010(Wallace et al , 2011. Additional studies on L1 as a modifier uncovered a novel role for L1 in promoting the migration and differentiation of ganglion cell precursors in the distal gut (Anderson et al 2006;Turner et al 2009), thus illustrating the power of modifier gene studies in identifying gene functions and cellular mechanisms.…”
mentioning
confidence: 75%
“…It is highly expressed on neurons in developing neural systems including neural crest cells. L1 plays an essential role in the chain migration and differentiation of neural crest cells (Anderson et al, ; Turner et al, ).…”
Section: Teratogens Disturb Neural Crest Cellsmentioning
confidence: 99%
“…It is highly expressed on neurons in developing neural systems including neural crest cells. L1 plays an essential role in the chain migration and differentiation of neural crest cells (Anderson et al, 2006;Turner et al, 2009). Ethanol inhibits L1 function by binding directly to L1 through a small hydrophobic pocket on its extracellular domain (Ramanathan et al, 1996;Arevalo et al, 2008;Dou et al, 2011), redistributing L1 within the membrane on lipid rafts (Tang et al, 2011), and interfering with both L1 mediated signaling (Bearer, 2001;Tang et al, 2006;Yeaney et al, 2009), and L1 mediated cell-cell adhesions (Ramanathan et al, 1996).…”
Section: Ethanol Exposure Affects Neural Crest Cellsmentioning
confidence: 99%